Ideas, Images, and Methods of Portrayal - Andrew Rippin (International Institute of Islamic Thought, 2007)
This ambitious collection of sixteen essays (plus an introduction by the editor) ranges widely across Islamic history and scholarly disciplines. The unifying theme is reflected in the title: Muslim texts are examined for their conceptual frameworks as conveyers of a cultural ethos. While some essays are more successful than others in enunciating this theme’s more theoretical aspects, the range of topics covered means that most readers will find something of interest and relevance and will likely be stimulated to apply the methods of analysis to their own area of study. Sebastian Günther’s introduction does an admirable job of highlighting each essay’s contribution to creating an overall picture of Muslim intellectual history and the “cultural specificity of Islam that facilitated the advancement of intellectual life and the formation of ‘modern’ societies” (p. xiv) by paying attention to the ideas, forms, content, and impact of textual artefacts from the eighth through the fourteenth centuries. Stephan Dähne begins the volume by focusing on the Qur’an and its use in political speeches attributed to Abu Hamza al-Shari (d. 747), Abdullah ibn al-Zubayr (d. 692), Uthman ibn Hayyan al-Murri (d. after 713), and Abdallah ibn Tahir (d. 844). Ute Pietruschka then deals with the Christian community’s literary activity under the Umayyads as it developed in Syriac (and emerged in Arabic), maintained the Byzantine tradition, and was impacted by Islam. Keeping with the Christian theme, Sandra Toenies Keating discusses the work of the Christian apologist Abu Ra’ita (d. ca 835) and his attempt to defend Biblical scripture from the Muslim charge of falsification (tahrif) ...